Induction of systemic resistance by leaf extract of Clerodendrum aculeatum in sunnhemp against sunnhemp rosette virus - VARSHA, H.N. VERMA and (Indian Phytopathology, 2002)
Concentrated preparations of a few plant extracts induce complete/partial systemic resistance in several crops against viruses by inducing general defensive reactions in susceptible plants as evidenced by the production of virus inhibitory agent. Diluted preparation of Clerodendrum aculeatum (CA), one such systemic resistance inducer, on priming with certain proteinaceous modifiers (CA-M) became as effective as concentrated preparation. The proteinaceous modifiers besides enhancing activity also prolonged the durability of induced resistance. The response of (CA-M) was thus more persistent. In the present communication, it has been shown that Crotalaria juncea plants can be protected against systemic infection by sunnhemp rosette virus by treatment with CA-M.